Discovery of a fourth species of Shaanxiana (Lepidoptera: Lycaenidae: Theclinae) from China - Huang, Hao (Zootaxa, 2016)
Shaanxiana langi sp. n. (Theclinae: Theclini), a fourth species of the genus Shaanxiana, is described from Guangxi province, China. It is similar to the recently described S. australis from Guangdong, but S. langi males can be distinguished from the latter by their lack of orange scales within the underside submarginal wing markings, and the medially protruding uncus of the genitalia. The female is notable for its extensive pale blue upperside wing coloration, requiring re-characterization of the genus with respect to sexual dimorphism. Both male and female genitalia of S. langi sp. n. are illustrated and described in detail, together with S. takashimai.